The influences of initially induced inhomogeneity over the dynamics of mismatched intense charged beams - Nunes R.P. (2010)
Although undesired in many applications, the intrinsic spurious spatial inhomogeneity that permeates real systems is the forerunner instability that leads high-intensity charged particle beams to its equilibrium. In general, this equilibrium is reached in a particular way, by the development of a tenuous particle population around the original beam, conventionally known as the halo. In this direction, the purpose of this work is to analyze the influence of the magnitude of initial inhomogeneity over the dynamics of quasi-homogeneous mismatched beams. For that, all beam constituent particles, which are initially disposed in an equidistant form, suffer a progressive perturbation through a noise of a variable amplitude. Beam quantities are quantified as functions of the noise amplitude, which indirectly is assumed a consistent measure of the initial beam inhomogeneity. The results have been obtained by the means of full self-consistent N-particle beam numerical simulations and seem to be an important complement to the investigations already carried out in prior works.